Desenvolvimento da Tecnologia de Soldagem do Titânio pelo Processo TIG Orbital no Segmento Aeroespacial Brasileiro - Parte 2: Caracterização das Juntas Soldadas - Orlowski de Garcia, Jose Augusto (2007)
In this work, three welding programs for orbital TIG previously developed were used, using pulsed current and increasing speed (M), constant current (#B) and pulsed current and decreasing current (#C). One of those should be used for the propulsion system of the satellite CBERS (CHINA-BRAZIL EARTH RESOURCES SATELLITE). Welded joints using tubes of commercially pure titanium were obtained with these procedures, which were characterized by means of mechanical and metallographic tests. The obtained results show that the three welding procedures produce welded joints free of defects and with adequate shape. Although small differences on mechanical properties and microstructure have been observed, the three welding programs attained compatible results with international standards used in the aerospace segment. The welding program #B, due the reduced heat input used, was considered to obtain slightly advantage over the others.